Pelatihan Penanganan Gangguan dan Kerusakan Rem Sepeda Motor di Desa Ketosari Kecamatan Bener Kabupaten Purworejo - Widiyatmoko Widiyatmoko; Aci Primartadi; Mike Elly Anitasari; Dwi Djatmoko (FKIP, Universitas Palangka Raya, 2024)
Ketosari Bener Purworejo Village is geographically one of the villages with narrow roads, with steep inclines and descents. Under these conditions, of course every vehicle, whether car or motorbike, that passes this road must be in good condition. A good engine condition is not enough if it is not supported by a good braking system. The condition of the engine and the performance of the brake system must be ensured that there is no interference or damage. This service activity aims to provide knowledge and information as well as practical or light skills to overcome problems and damage to motorbike brakes to the community. Service activities begin with preparation, implementation and reflection on activities. The training activities were carried out in the form of workshops, material presentations and questions and answers. The evaluation results obtained were: 1) Implementation of activities at 90%, 2) Mastery of resource material with a score of 95%, 3) Usefulness of the material or program with a score of 92%, and 4) Participant satisfaction with a score of 89%.